Brazilian children's quality of life during the COVID-19 pandemic: analysis of contextual factors and dimensions - Tainá Ribas Mélo; Luize Bueno de Araujo; Marcos Claudio Signorelli; Paulo Ricardo Bittencourt Guimarães; Vera Lúcia Israel (Sociedade de Pediatria de São Paulo, 2024)
ABSTRACT Objective: The aim of this study was to investigate the contextual factors associated with the quality of life (QOL) of Brazilian children aged 0-12 years during the strict period of social isolation. Methods: This observational cross-sectional study was conducted between July and September 2020 using an online questionnaire on QOL-related family factors and the Pediatric Quality of Life Inventory (PedsQL™). Results were analyzed by multinomial logistic regression analysis. Results: The sample had 849 children, mostly from the South Region of Brazil (75%), white (83%), with typical development (79%), sedentary (68%), using screen (85%) for >3 h/day (44%). Their mothers were their main caregivers (90%). The following variables were significantly associated with high scores of QOL: typical health status (OR 2.38; 95%CI 1.60-3.55; screen time ≤2 h/day (OR 1.62; 95%CI 1.17-2.24); social distancing considered as "easy" (OR 1.67; 95%CI 1.20-2.32), and stimulation of the child by the family (OR 1.93; 95%CI 1.08-3.45). Conclusions: This study indicates that the family context can influence children's QOL, especially during the COVID-19 pandemic and home environment reorganization.